Role of home visits by volunteer community health workers: to improve the coverage of micronutrient powders in rural Bangladesh. Issue Volume 24:Issue S1(2021) (5th April 2021) - Sarma, Haribondhu; Mbuya, Mduduzi NN; Tariqujjaman, Md; Rahman, Mahfuzur; Askari, Sufia; Khondker, Rudaba; Sultana, Sabiha; Shahin, Shaima Arzuman; Bossert, Thomas J; Banwell, Cathy; Neufeld, Lynnette M; Ahmed, Tahmeed; et al.
Abstract: Objective: We assessed the role of home visits by Shasthya Shebika (SS) – female volunteer community health workers (CHWs) – in improving the distribution of micronutrient powder (MNP), and explored the independent effects of caregiver–provider interaction on coverage variables. Design: We used data from three cross-sectional surveys undertaken at baseline ( n 1927), midline ( n 1924) and endline ( n 1540) as part of an evaluation of a home fortification programme. We defined an exposure group as one that had at least one SS visit to the caregiver's household in the 12 months preceding the survey considering three outcome variables – message (ever heard), contact (ever used) and effective coverage (regular used) of MNP. We performed multiple logistic regressions to explore the determinants of coverage, employed an 'interaction term' and calculated an odds ratio (OR) to assess the modifying effect of SS's home visits on coverage. Settings: Sixty-eight sub-districts from ten districts of Bangladesh. Participants: Children aged 6–59 months and their caregivers. Results: A home visit from an SS positively impacts message coverage at both midline (ratio of OR 1·70; 95 % CI 1·25, 2·32; P < 0·01) and endline (ratio of OR 3·58; 95 % CI 2·22, 5·78; P < 0·001), and contact coverage both at midline (ratio of OR 1·48; 95 % CI 1·06, 2·07; P = 0·021) and endline (ratio of OR 1·74; 95 % CI 1·23, 2·47; P = 0·002). There was no significant effect of a SS's home visit on effective coverage. Conclusions: The households visited by BRAC's volunteer CHWs have better message and contact coverage among the children aged 6–59 months.